2011
DOI: 10.1186/1471-2164-12-490
|View full text |Cite
|
Sign up to set email alerts
|

Skin healing and scale regeneration in fed and unfed sea bream, Sparus auratus

Abstract: BackgroundFish scales are an important reservoir of calcium and phosphorus and together with the skin function as an integrated barrier against environmental changes and external aggressors. Histological studies have revealed that the skin and scales regenerate rapidly in fish when they are lost or damaged. In the present manuscript the histological and molecular changes underlying skin and scale regeneration in fed and fasted sea bream (Sparus auratus) were studied using a microarray 3 and 7 days after scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 81 publications
5
48
0
Order By: Relevance
“…Transcriptional responses to damage have also been studied in non-mollusc species. In a microarray experiment investigating scale regeneration (a type of biomineralisation) in sea bream, Vieira et al (2011) found 769 differentially expressed genes after 3 days but only 21 differentially expressed after 7 days. Taken together with the results of the present study, damage-repair experiments emphasise the importance of timing in biomineralisation studies.…”
Section: Experiments One: Transcriptional Profiling Of Damage Responsementioning
confidence: 99%
“…Transcriptional responses to damage have also been studied in non-mollusc species. In a microarray experiment investigating scale regeneration (a type of biomineralisation) in sea bream, Vieira et al (2011) found 769 differentially expressed genes after 3 days but only 21 differentially expressed after 7 days. Taken together with the results of the present study, damage-repair experiments emphasise the importance of timing in biomineralisation studies.…”
Section: Experiments One: Transcriptional Profiling Of Damage Responsementioning
confidence: 99%
“…Keratocytes can cover fish skin wound surfaces with a new protective layer of cells within hours after wounding by rapid migration from the surrounding wound margins [66,67]. In addition to their migratory activity, different cell types present in fish epidermis are shown to internalize particular matter such as bacteria and other particles.…”
Section: Teleost Skinmentioning
confidence: 99%
“…Fish skin differs in several aspects from mammalian skin and the functional divergence between skin in a terrestrial and aquatic environment is presumably underpinned by significant divergence in molecular and cellular processes. While in human skin the primary physical barrier that confers protection is the stratified epidermis that is composed of dead keratinized cells, in fish the epidermis is composed of metabolically active cells with little keratinization [58]. Goblet cells and club cells produce mucous rich in proteases, mucins, immunoglobulins and antimicrobial peptides (AMPs) that protect the living epidermis of the fish integument.…”
Section: Introductionmentioning
confidence: 99%